Hubungan Prominence of Product Placement dan Placement Modality dengan Placement Recall di Serial Drama Korea ‘Goblin’ - Cindy Aprilia Mardha; Nuriyatul Lailiyah (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is aimed at finding a relationship between prominence of product placement and placement modality with placement recall in Korean serial drama Goblin. The theory used is the theory of isolation and the theory of dual coding. The sampling technique uses nonprobablity sampling conducted purposively with a total sample of 35 people with criteria is a Korean drama enthusiast, have watched the Goblin drama series, aged 15-25 years and live in the city of Semarang. Testing is done by Chi Square test Fisher Exact Test formula. The results of this study indicate that there is no relationship between prominence of product placement and placement recall. These results are obtained from the significance of the hypothesis test which shows the number 1,000 (1,000> 0.05) which means it is not significant for the F&B category. Whereas the electronic and toiletries and cosmetics categories cannot be tested statistically. The next results show that there is also no relationship between placement modality and placement recall. Hypothesis test results for the F&B category showed a significance number of 0.648 (0.648> 0.05) and an electronic category of 0.400 (0.400> 0.05), which means not significant. While the toiletries and cosmetics category cannot be tested statistically.